Vacuum high-temperature refining of carbon materials using NaCl vapors as a transport and reaction medium - Kravtsov, Ya.V.; Gurin, I.V.; Bukolov, A.N.; Gribanov, Yu.A.; Kolosenko, V.V. (Вопросы атомной науки и техники, 2020)
One of the main requirements to carbon materials is their purity. The authors have proposed and experimentally tested a new method for vacuum-thermal refining of carbon materials using NaCl vapor as an activator. It is experimentally confirmed that this method allows increasing the refining process efficiency and decreasing the energy consumption. The proposed method can be an alternative to modern methods of chlorine- and fluorine thermal refining that permits to exclude the use of hazardous reagents. Однією з основних вимог до вуглецевих матеріалів є їх чистота. В роботі представлена та експериментально перевірена нова методика вакуумно-термічної рафінації вуглецевих матеріалів з використанням в якості активатора NaCl. Експериментально підтверджено, що використання такої методики дозволяє підвищити ефективність та зменшити енергоємність процесів рафінації. Запропонована методика може стати альтернативою сучасним методам хлор- та фтортермічної рафінації, тим самим дозволить виключити використання шкідливих та небезпечних реагентів. Одним из основных требований к углеродным материалам является их чистота. В работе представлена и экспериментально проверена новая методика вакуумно-термической рафинации углеродных материалов с использованием в качестве активатора NaCl. Экспериментально подтверждено, что использование такой методики позволяет повысить эффективность и уменьшить энергоемкость процессов рафинации. Предложенная методика может стать альтернативой современным методам хлор- и фтортермической рафинации, тем самым позволит исключить использование вредных и опасных реагентов.